The book of Lord Shang : apologetics of state power in early China - Shang, Yang, -338 B.C.; Pines, Yuri (New York : Columbia University Press, 2017)
Compiled in China in the fourth-third centuries B.C.E., The Book of Lord Shang argues for a new powerful government to penetrate society and turn every man into a diligent tiller and valiant soldier. Creating a "rich state and a strong army" will be the first step toward unification of "All-under-Heaven." These ideas served the state of Qin that eventually created the first imperial polity on Chinese soil. In this new translation, The Book of Lord Shang's intellectual boldness and surprisingly modern-looking ideas shine through, underscoring the text's vibrant contribution to global political
11. Establishing the Roots; 12. Military Defense; 13. Making Orders Strict; 14. Cultivation of Authority; 15. Attracting the People; 16. Essentials of Punishments; 17. Rewards and Punishments; 18. Charting the Policies; 19. Within the Borders; 21. Protecting from Robbers; 22. External and Internal; 23. Ruler and Ministers; 24. Interdicting and Encouraging; 25. Attention to Law; 26. Fixing Divisions; Fragment of "Six Laws."
Translated from the Chinese.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Philosophy, Chinese -- Early works to 1800.; Political science -- China -- Early works to 1800.; China -- Politics and government -- To 221 B.C. -- Early works to 1800.; Philosophie chinoise -- Ouvrages avant 1800.; Chine -- Politique et gouvernement -- Jusqu'à 221 av. J.-C. -- Ouvrages avant 1800.; PHILOSOPHY -- Political; Philosophy, Chinese; Political science; Politics and government; China; To 221 B.C.; Early works